Preterm birth, unplanned hospital contact and mortality in infants born to teenage mothers in five countries: a cross-country comparison using linked administrative data - Harron, Katie; Verfuerden, Maximiliane; Ibiebele, Ibinabo; Liu, Can; Kopp, Alex; Guttmann, Astrid; Ford, Jane; Hjern, Anders; van der Meulen, Jan; Gilbert, Ruth (International Journal of Population Data Science, 2018)
Background Children born to teenage mothers have greater healthcare needs than those born to mothers in their 20s and older, including higher rates of hospitalisation in childhood. Objectives We performed a cross-country comparison of maternal agerelated inequalities in infant outcomes in England, Scotland, Sweden, New South Wales (NSW; Australia) and Ontario (Canada). Methods We used administrative hospital data capturing 3,002,749 singleton births surviving to discharge between 2010-2014 (2008-2012 for Sweden). We compared preterm birth (24-37 weeks of gestation), unplanned hospital admissions, emergency department visits, and mortality within 12 months of postnatal discharge, according to maternal age. Findings Infants born to teenage mothers experienced higher rates of preterm birth, unplanned admissions, ED visits, and mortality compared with older mothers in all countries. Despite variation in the distribution of maternal characteristics between countries, inequalities according to maternal age were similar. Infants of teenage mothers were between 1.37 (95% CI for risk ratio 1.28-1.47, Sweden) and 1.56 (95% CI 1.49-1.64, NSW) times more likely to have 1 unplanned hospital admission and between 2.25 (95% CI 1.92-2.64, England) and 3.87 (95% CI 2.07-7.36, Sweden) times more likely to die, compared with those born to mothers aged 30-34. Conclusions A similar excess of adverse outcomes was observed for teenage mothers in all five countries, despite different prevalence rates and support for young families. Public health strategies are needed to address these inequalities.